Konsep Murabahah dan Aplikasinya dalam Perbankan Syariah - Hikmah Dwi Astuti (Institut Agama Islam Agus Salim Metro Lampung, 2020)
ABSTRACT In practice more Islamic banks use murabahah contracts than other contracts. Endemic characteristics that are certain in the amount of installments and margins also give rise to the perception that the use of murabahah contracts can reduce the level of risk of financing. In fiqh there is indeed no portfolio arrangement in Islamic financial institutions. Then institutionally, the choice of murabahah contract compared to other contracts is the most attractive, profitable and least risky option so that the bank is basically allowed to prioritize murabahah in its product contract. Keyword: Murabahah, Islamic Bank, Financing.